The Effect of the Increase in the Selling Value of Tax Objects - Land and Building Tax (NJOP - PBB) on the Transfer of Land Rights at the Notary Office - PPAT in Blora Regency - Bryant Manggala Retnanindyani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this study is to determine and analyze: 1). The process of transferring land rights to the Blora Regency Regional Regulation Number 15 of 2018 at the Notary Office - Land Deed Making Official (PPAT). 2) The effect of the increase in the Selling Value of Tax Objects - Land and Building Tax (NJOP - PBB) on the transfer of land rights 3) Barriers and efforts with the increase in the Selling Value of Tax Objects - Land and Building Tax (NJOP - PBB) on the transition process land rights at the Notary Office - PPAT Elizabeth Estiningsih, SHThe approach method in this research is juridical normative, namely research that emphasizes the science of law and tries to examine the rules of law that apply to the subject matter. The data used are primary and secondary data obtained through interviews and literature studies, while the data analysis method is carried out by qualitative descriptive analysis.The results of the research resulted in the following conclusions: 1) In the registration of the transfer of their rights, the applicant can be represented by PPAT. Based on the Regional Regulation of Blora Regency Number 15 of 2018, one of the conditions for the transfer and registration of rights to land and / or buildings is proof of payment of fees for the acquisition of land and building rights (BPHTB). 2) The increase in the Sales Value of Tax Objects - Land and Building Tax (NJOP - PBB) certainly affects the process of transferring land rights, because it is not uncommon for the transaction value submitted by taxpayers to be deemed inappropriate by tax officials, so it is not uncommon for tax officials to be in the process. verification / validation, requesting that the transaction value be changed and adjusted according to the tax officer's assessment. 3) The Petitioner has objections to the tax to be paid. Where the tax value to be paid is very high, the NJOP also increases every year so that with an increasing NJOP, the tax to be paid is the estimated value determined by the BPPKAD exceeds the original sale and purchase value made by the parties. The Blora Regency Government must issue standard regulations so that there are no differences in the calculation of BPHTB.